Myelin degeneration induced by mutant superoxide dismutase 1 accumulation promotes amyotrophic lateral sclerosis. Issue 10 (10th July 2019) - Kim, Suhyun; Chung, Ah‐Young; Na, Ji E.; Lee, Se J.; Jeong, Sang H.; Kim, Eunmi; Sun, Woong; Rhyu, Im J.; Park, Hae‐Chul
Abstract: Myelin is a specialized membrane that wraps around nerve fibers and is essential for normal axonal conduction in neurons. In the central nervous system, oligodendrocytes are responsible for myelin formation. Recent studies have reported pathological abnormalities in oligodendrocytes in human patients with amyotrophic lateral sclerosis (ALS) and a mouse model of ALS expressing the G93A mutation of the human superoxide dismutase 1 (mtSOD1). However, it is unclear whether oligodendrocyte pathology in ALS represents the primary dysfunction induced by mtSOD1 and how mtSOD1 contributes to oligodendrocyte degeneration and ALS pathogenesis. We analyzed GAL4‐VP16‐UAS transgenic zebrafish selectively expressing mtSOD1 in mature oligodendrocytes. We observed that mtSOD1 directly induced oligodendrocyte degeneration by disrupting the myelin sheath and downregulating monocarboxylate transporter 1 (MCT1), thereby causing spinal motor neuron degeneration. Pathological changes observed in this transgenic zebrafish were similar to the pathology observed in the SOD1 G93A mouse model of ALS, which is characterized by expression of mtSOD1 in all cells. In addition, oligodendrocyte dysfunction induced by mtSOD1 was associated with anxiety‐related behavioral abnormalities, learning impairments, and motor defects in the early symptomatic stage. We also found that treatment with potassium channel inhibitors rescued behavioral abnormalities without rescuing MCT1 expression, suggesting that myelin disruption induces behavioral abnormalities independently of MCT1. These results indicate that mtSOD1‐induced dysfunction of mature oligodendrocytes is sufficient to induce motor neuron degeneration, thus informing future therapeutic strategies targeted at oligodendrocytes in ALS. Main points: Expression of mutant SOD1 in mature oligodendrocytes directly induces degeneration of oligodendrocytes, leading to motor neuron death. Oligodendrocyte dysfunction induced by mutant SOD1 is associated with anxiety‐related behavioral abnormalities.